A study of the aromaticity and ring currents of azaacepentalenes. (20th March 2019) - Lu, Fang; Kerim, Ablikim
Abstract: Using the topological resonance energy (TRE) method, a computational study has been carried out on the aromaticity of an acepentalene (cyclopenta[ cd ]pentalene) molecule upon the replacement at different positions of some of its carbon atoms by two pyrrole‐like nitrogen atom isomers and by one or more pyridine‐like nitrogen atom isomers. The relative aromaticity of the isomers was explained by the topological charge stabilization rule. Each of the resultant azaacepentalene isomers shows lower aromaticity relative to the acepentalene dianion. We found that the magnitudes of the global aromaticity of these azaacepentalenes are solely determined by the position of the two substituted pyrrole‐like nitrogen atoms. Bond resonance energy (BRE) and circuit resonance energy (CRE) indices were used to evaluate the local aromaticity of each of the distinct azaacepentalenes. Our BRE and CRE results show that all of these compounds are primarily stabilized by the 6π electron conjugated system. Our global and local aromaticity results are compared with the other aromaticity indices as reported in the literature. Regarding the order of aromaticity, some discrepancies were found between the magnetic and energic criteria for aromaticity. The ring current (RC) analyses were made using the Hückel‐London model. The RC results revealed that all of the compounds were diatropic, and the quantitative differences in their degrees of diatropicity were quite consistent with the experimental data on 1 H NMR chemical shifts. Abstract : The global aromaticity of acepentalene, of its doubly charged ions, as well as of the 104 related types of azaacepentalene isomers has been investigated using the topological resonance energy method. All the azaacepentalenes exhibit lower global aromaticity than the acepentalene dianion. Their local aromaticity has been investigated using the bond resonance energy (BRE) and circuit resonance energy (CRE) indices. Our BRE and CRE results show that azaacepentalenes are stabilized primarily by the 6π electron conjugated system.